Improvements in fitness and motor performance from the first to fifth grade in Basel - Lichtenstein, Eric; Nebiker, Lukas; Faude, Oliver (Current Issues in Sport Science (CISS), 2023)
Introduction A well-developed motor performance is one key aspect of being able to participate in organised sports and to establish and maintain lifelong physical activity. Furthermore, a good fitness is an early indicator of beneficial health in adult life. The development of motor performance and fitness can be influenced by many facets like education, environment, nutrition and family habits. It could be important to identify factors that are negatively associated with motor development and fitness in order to propose interventions tackling them or specifically targeting disadvantaged children. The aim of this study is to identify intrinsic and extrinsic factors associated with the magnitude of motor performance and fitness development from the first to fifth grade in children in the city of Basel. Methods Children were tested in the first and the fifth grade for motor performance and anthropometrics. Parents were asked in the first grade to fill out a questionnaire. Motor performance tests included 20-meter shuttle run, 20-meter sprint, balancing backwards and side hopping tasks. The questionnaire asked among other things about socio economic status (SES) of the household in seven categories (up to CHF 2,000 per month, 2,000-3,000, 3,000-4,000, 4,000-5,000, 5,000-7,000, 7,000-9,000 and more than 9,000). Age, sex, height, BMI and SES were linearly regressed with changes in motor performance while controlling for baseline performance and the other factors. Mean and standard deviations are presented for descriptive data and effect sizes (standardized beta coefficients) for regression results. Results Thousand five-hundred and sixty-four children were assessed in both grades and 418 questionnaires were returned. Children were 50% male, 7.4 (±0.4) years of age in first grade, BMI was 16.3 (±2.4) kg/m2, and SES was 5.4 (±1.8). Motor performance improved by 60.2 (±77.3)%, 57.9 (±134)%, 71.3 (±39.2)% and 14.1 (±7.45)% for shuttle run, balancing backwards, side hopping and sprint, respectively. The proportion of overweight and obese children increased from 18.8 (±3.9) to 25.8 (±4.4)% and from 10.4 (±3.0) to 13.3 (±3.4)%, respectively. Neither age (β < 0.12) nor SES (β < 0.08) were meaningfully related to improvements in motor performance or fitness. Girls showed slightly larger improvements in sprint (β = 0.12) and balance (β = 0.08) performance while boys had larger improvements in shuttle run (β = 0.39) and jumping (β = 0.14) performance. Girls also showed substantially larger gains in BMI than boys (β = 0.68). BMI in first grade was negatively associated with improvements in shuttle run (β = 0.23) and sprint (β = 0.17) performance, but also slightly with balancing (β = 0.07) and jumping (β = 0.08) performance. Discussion/Conclusion A high BMI in first grade is negatively associated with development of motor performance and fitness and respective children should receive additional attention. Fortunately, children from economically disadvantaged families or younger children at school entry, showed a normal development in motor performance and fitness. The difference between boys and girls could be related to different developments in body composition for body weight related parameters (jumping and fitness). Based on these results, targeting interventions (exercise or nutrition) at children with a high BMI in first grade might be advisable, regardless of SES, age or sex.